Analisis Kepuasan Anggota Nasabah Terhadap Pelayanan Tabungan DI BMT NU Cabang Silo - Suprianik, Suprianik; Anugrah Arif Ivandi; Muchammad Reza Syauqi Rosydi; Sukron Riski Alfandra (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to analyze the level of customer satisfaction with savings services at BMT NU Silo Branch. In facing competition in the Islamic finance industry, customer satisfaction is an important factor that contributes to loyalty and business sustainability. The method used in this research is descriptive qualitative, with data collection through interview and observation techniques. The research results show that the majority of customers are satisfied with the services provided, especially due to the implementation of the 3S principle (Sapa, Smile, Salam), the flexibility of the savings system, and transparency in the distribution of results. Superior products, such as Mudharabah Savings (TABAH), are the main choice for customers because they offer convenience in transactions and competitive returns. Based on these findings, it is recommended that BMT NU Silo Branch continue to improve service quality in order to maintain and increase customer loyalty.